PENGOLAHAN BATOK KELAPA MENJADI POT TANAMAN UNTUK PENANAMAN TANAMAN HIAS ANGGREK DALAM UPAYA PEMANFAATAN LIMBAH ALAM - Pramudito, Baskara; Safitri, Wasila; Putro, Die Bhakti Wardoyo (Sekolah Tinggi Ilmu Ekonomi AMA, 2025)
This study aims to examine the utilization of coconut shell waste as plant pots for planting ornamental orchids. Coconut shells, which are often considered as waste, have great potential as an environmentally friendly and sustainable planting medium. In this study, coconut shells were processed into plant pots through several stages, including cleaning, drying, and shaping. Coconut shell pots were tested for planting ornamental orchids and compared with conventional plastic pots. The results showed that coconut shell pots were able to maintain soil moisture better and provide additional nutrients for plants. In addition, the use of coconut shell pots also reduces plastic waste and supports sustainable agricultural practices. This study concludes that coconut shells are an effective and environmentally friendly alternative for plant pots, especially for planting ornamental orchids.